2022
DOI: 10.3390/math10193531
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of FinTech with Perceived Mediators in Consumer Financial Satisfaction with Cashless Payments

Abstract: The purpose of this paper is to investigate the association between FinTech payments and consumer financial satisfaction with cashless payments using data from the 2017 China Household Finance Survey. This study defines computer payment and mobile terminal payment using a cell phone or pad as payments with FinTech. The results indicate that payments with FinTech are positively associated with financial satisfaction with cashless payments. Furthermore, this result holds in the eastern and central groups of Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The y t represents the year-fixed effect, and stands for state dummies. Following the specifications of [ 40 ]; control variables incorporate age, ethnicity (Two categories: white and non-white), marital status (Two types: married and not married), the number of children, income, work status (0—unemployed, and 1—employed), risk attitude (From 1—not at all willing to take any risk to 10—very willing to take risks), financial education (0—no financial education, and 1—have financial education), perceived financial capability (From 1—very low to 7—very high), perceived math capability (From 1—strongly disagree that I am pretty good at math to 7—strongly agree that I am pretty good at math), owning house property (0—don't have a house, and 1—have a house), and credit rating (1—very bad, and 5—very good). Moreover, represents the financial knowledge a respondent has.…”
Section: Methodsmentioning
confidence: 99%
“…The y t represents the year-fixed effect, and stands for state dummies. Following the specifications of [ 40 ]; control variables incorporate age, ethnicity (Two categories: white and non-white), marital status (Two types: married and not married), the number of children, income, work status (0—unemployed, and 1—employed), risk attitude (From 1—not at all willing to take any risk to 10—very willing to take risks), financial education (0—no financial education, and 1—have financial education), perceived financial capability (From 1—very low to 7—very high), perceived math capability (From 1—strongly disagree that I am pretty good at math to 7—strongly agree that I am pretty good at math), owning house property (0—don't have a house, and 1—have a house), and credit rating (1—very bad, and 5—very good). Moreover, represents the financial knowledge a respondent has.…”
Section: Methodsmentioning
confidence: 99%
“…Credit card is an important embodiment of FinTech and digital access affects the corresponding use perception (Grodzicki and Koulayev, 2021). Previous studies have shown that perceived convenience and perceived popularity influence consumers' evaluation of the credit card payment process and then change their credit card behavior (Chen and Jiang, 2022). On the one hand, better digital access is conducive to the more convenient use of credit cards because the process of using credit cards is smoother (Alao and Sorinola, 2015).…”
Section: Hypothesesmentioning
confidence: 99%
“…Application users are very concerned about the risks posed by the security of applications used for financial transactions in the online retail sector (Hsiao, 2021;Nizam, Hwang, & Valaei, 2019). Researchers have examined how a person's perception related to the risk impacts whether they use their mobile wallet to make cashless payments (F. Chen & Jiang, 2022;Rahman, Ismail, Bahri, & Rahman, 2022). Although mobile payments are popular and practical (Nizam et al, 2019;Yan, Tan, Loh, Hew, & Ooi, 2021), security and privacy concerns result from such transactions (Aji, Berakon, & Md Husin, 2020;Kasirye & Masum, 2021).…”
Section: Perceived Riskmentioning
confidence: 99%